Varietal development and the effectiveness of seed sector policies: The case of rice in Nigeria - Takeshima, Hiroyuki; Maji, Alhassan (International Food Policy Research Institute, 2016)
Seed is an essential input in agriculture, and the availability of quality seed of superior varieties is often critical for improved food security and poverty reduction in developing countries like Nigeria. However, while the Nigerian government recognizes the importance of improving seed availability, its recent focus in the seed sector has mostly been on improving seed quality rather than on varietal development. This report argues that this is partly due to a knowledge gap regarding the relationship between varietal technology levels and the effectiveness of seed sector policies. We first provide a brief conceptual discussion on how the effectiveness of selected seed sector policies, such as certification, subsidies, and private sector promotion, may depend on underlying varietal technology levels. Using rice as an example, we then provide key historical and international perspectives on how varietal technology development by the public sector through intensive rice breeding had pre-ceded the expansion of seed certification and testing, and show that there still is a substantial need for the Nigerian government to develop improved rice varieties through intensified domestic plant breeding in order for its seed certification and seed subsidy programs to be more effective.